Case report: A rare case of malacoplakia resembling a malignant tumor of the cervix: a case report and review of the literature - Li, Jiaorong; Mi, Jiaying; Wang, Juanjuan; Zhuo, Zhihong (Frontiers in Medicine, 2024)
Malacoplakia is a rare chronic granulomatous disease that mostly affects the gastrointestinal tract and urinary tract of immunocompromised patients; malacoplakia rarely effects the female reproductive tract. Here, we report a 56-year-old patient who underwent thymectomy for thymoma and myasthenia gravis prior to developing cervical and vaginal malacoplakia. The patient presented with recurrent vaginal bleeding.. We discovered that there were alterations in the cervical cauliflower pattern during colposcopy, which is suggestive of cervical cancer. Pathological examination of the lesion tissue showed that a large number of macrophages aggregated, and M-G bodies with concentric circles and refractive properties were observed between cells.Immunostaining for CD68 and CD163 was positive, and special staining for D-PAS and PAS was positive. The discovery of Escherichia coli in bacterial culture can aid in the diagnosis of malacoplakia. Following surgery, we performed vaginal lavage with antibiotics in addition to resection of local cervical and vaginal lesions. This study provides a fresh perspective on the management of genital malacoplakia.